An efficient and robust access method for indexing of spatial objects - Mihran S. Grigoryan (Изд-во НАН РА)
There are considered the problems connected with the organization of probably faster and effective access to geometrical objects (points, lines, and polygons), coded in standard way in object-relational databases. For maintenance of effective access the well-known method of so-called Rtrees is often used; improved versions of this method which allow to raise the speed of access to objects of the mentioned specified type in comparison with usually applied variants of a method of R-trees are considered. For achievement of the mentioned purpose there are entered into considerations R’- Trees, which represent certain updating of R-Trees, and R’- Trees allow to model methods of linear and quadratic R-Trees of Gutman, and the variant of R-Trees offered by Green. So a number of advantages of R’-Trees in comparison with R-Trees are established.
Keywords: Mathematics; Computer software